PEMBARUAN HUKUM PIDANA MELALUI AKTUALISASI NILAI-NILAI PANCASILA BERORIENTASIKAN PENDEKATAN RELIGIUS - Fatoni, Syamsul (IAIN Tulungagung, 2015)
The reformation of criminal law can be done through the reformation ofsubstantial norm as well as the reformation of cultural value includingPancasila. Therefore, it is emergent to explore the law which is based oncultural value, morality, and religion including reactualization of Pancasilato maintain a harmonious life.Kata kunci: Pembaruan, Nilai-Nilai Pancasila, Religius